Perancangan UI/UX Sistem Informasi Multi Payment Pada Aplikasi Alfagift Dengan Pendekatan Design Thinking - Fitriyanti, Fitriyanti; Dudi Awalludin; Priatna, Apit; Herina, Nansy (LPPM STMIK Rosma, 2025)
Alfamart as one of the retail companies in Indonesia is taking advantage of e-commerce developments by creating mobile-based applications. Alfagift is an application under the auspices of PT. Source Alfaria Trijaya, tbk. Alfagift is a shopping application that makes it easy for customers to shop from home and orders will be delivered to their homes without shipping costs or using the store pick-up method. However, the Alfagift payment service feature does not yet have many service options that Alfagift users need. Therefore, the author is interested in analyzing and designing the display of the new multi-payment feature information system in the Alfagift application. The aim of this research is to improve the quality of service in the Alfagift application by designing a multipayment feature design so that it helps make it easier for users to make bill payment transactions using the features in the Alfagift application. This design uses the Design Thinking method whose stages include empathize, define, ideate, prototype and testing.